ANALISIS PERKEMBANGAN BUMDES SYARIAH USAHA BERSAMA DESA MAHATO SAKTI - Sri Wahyuni (Jurnal Ilmiah Cano Ekonomos, 2023)
Efforts to drive the village economy so that it is more advanced is through entrepreneurship in the village which is oriented towards studying the local potential of the village. Optimizing the utilization of local potential is one of the next steps in community selfhelp that utilizes local potential and resources. BUMDes is a business that was established based on the commitment of the village community to work together, work together and also build the people's economy which aims for the welfare and prosperity of the village community. The focus of this research is to find out the development of BUMDes Syariah Joint Ventures in Mahato Sakti Village. The research approach used by researchers in this study is a qualitative approach. The primary data sources are the Village Head, Village Treasurer, BUMDes Director, BUMDes secretary, and local community leaders. While secondary data include: data in the form of reports, documents, raw data and necessary data. Data collection instruments used in this study were interviews, observation and documentation studies. The data analysis method used in this research collects data, reduces data, presents data and draws conclusions. The results showed that the development of BUMDes Syariah Joint Venture Mahato Sakti Village experienced significant developments in the aspect of capital ownership and BUMDes business units as a booster for the economy of Mahato Sakti Village in order to realize community welfare.